PENDIDIKAN MORAL DAN KARAKTER: SEBUAH PANDUAN - Taher, Andi (Universitas Islam Negeri Raden Intan Lampung, 2014)
MORAL EDUCATION AND CHARACTER BUILDING : A HANDBOOK: Education Institutions have a very important task associated with moral and character development. Unfortunately, the various activities in schools are not enough to support the implementation of moral education. This book may become the main handbook for moral and character education in schools as it contains a very strong philosophical foundation accompanied by the clear strategies and techniques of implementation. Other than to support the activities in the classroom, this book also offers a detail and applicable formula of moral and character education outside the classroom, including efforts to develop character through sports activities